Cardiovascular events in adult polymyositis and dermatomyositis: a meta-analysis of observational studies. (16th November 2021) - Xiong, Anji; Hu, Ziyi; Zhou, Shifeng; Qiang, Yiying; Song, Zhuoyao; Chen, Huini; Xiang, Qilang; Zhang, Yan; Cao, Yuzi; Cui, Hongxu; Luo, Jie; Wang, Ye; et al.
Abstract: Objectives: We aimed to review whether PM and DM patients have an increased cardiovascular (CV) risk, including ischaemic heart disease (IHD), cerebrovascular accidents (CVA) and venous thromboembolism. Methods: We searched PubMed, Embase and the Cochrane database for relevant studies from inception to February 2021. Results: Twenty-two studies comprising 25 433 patients were included. With PM/DM vs general populations, the risk was significantly increased for CV events [relative risk (RR) = 2.37, 95% CI: 1.86, 3.02]. The RR of CV events for males with PM/DM was higher than for females (RR = 1.43; 95% CI: 1.17, 1.74). PM/DM patients followed for one to five years had a significantly higher CV risk than those followed for five to ten years (RR = 3.51, 95% CI: 1.95, 6.32). The risk was increased for North Americans (RR = 4.28, 95% CI: 2.57, 7.11), Europeans (RR = 2.29, 95% CI: 1.58, 3.31) and Asians (RR = 2.03, 95% CI: 1.41, 2.90). Our meta-analysis found that the elevated CV event risk was related to PM (RR = 2.35, 95% CI: 1.51, 3.66) and DM (RR = 2.55, 95% CI: 1.66, 3.93). Subgroup analyses showed that the risk was significantly increased for IHD (RR = 1.76, 95% CI: 1.40, 2.21), CVA morbidity (RR = 1.31, 95% CI: 1.03, 1.67) and ischaemic stroke (IS) (RR = 1.47, 95% CI: 1.26, 1.73), with no statistically significant increased risk of haemorrhagic stroke mortality (RR = 1.43, 95% CI: 0.92, 2.21). The CV event risk was increased for venous thromboembolism (RR = 4.60, 95% CI: 3.17, 6.66), deep venous thrombosis (RR = 5.53, 95% CI: 3.25, 9.39) and pulmonary embolism (RR = 5.26, 95% CI: 2.62, 10.55). Conclusion: This meta-analysis found that PM/DM patients had a ∼2.37 times increased CV risk, particularly males diagnosed in the previous five years. PM/DM may be an independent risk factor for developing IHD, IS, deep venous thrombosis and pulmonary embolism.